1994
DOI: 10.1016/0021-9290(94)91390-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related compliance of the lamina cribrosa in human eyes

Abstract: Aims-To investigate changes in the mechanical compliance of ex vivo human lamina cribrosa with age. Methods-A laser scanning confocal microscope was used to image the surface of the fluorescently labelled lamina cribrosa in cadaver eyes. A method was developed to determine changes in the volume and strain of the lamina cribrosa created by increases in pressure. The ability of the lamina cribrosa to reverse its deformation on removal of pressure was also measured. Results-Volume and strain measurements both dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 7 publications
3
52
2
2
Order By: Relevance
“…Several studies have suggested that the LC is stiffer in older ONHs. 24,25 This lower elasticity might be the cause of the reduced anterior LC displacement that we found, compared to Lee's study. However, we did not find a correlation between age and structural changes in our series.…”
Section: Discussionmentioning
confidence: 43%
“…Several studies have suggested that the LC is stiffer in older ONHs. 24,25 This lower elasticity might be the cause of the reduced anterior LC displacement that we found, compared to Lee's study. However, we did not find a correlation between age and structural changes in our series.…”
Section: Discussionmentioning
confidence: 43%
“…An age-related decline in the compliance of the lamina cribrosa, assessed using confocal scanning ophthalmoscopy, has been documented previously. 20 In certain susceptible eyes, this increase in the age-related thickness in the lamina beams may result in an exaggerated response to changes in intraocular pressure, leading to permanent deformation of the lamina cribrosa, and ultimately resulting in axonal loss.…”
Section: Discussionmentioning
confidence: 99%
“…The high imaging speed allows both the gross morphology and the small structures in the lamina cribrosa to be revealed because motion artifacts and motion induced discontinuities are reduced. Changes in the mechanical properties and shape of the lamina 29,30 are thought to lead to retinal ganglion cell death and the associated onset of glaucoma. The ability to investigate the structure of the lamina cribrosa, as well as track changes to the morphology over time, could prove to be important in understanding how the eye changes with age and ultimately lead to improved diagnostics and treatments for glaucoma.…”
Section: Ultrahigh Speed 3d Volumetric Acquisitions and Dense 2d Crosmentioning
confidence: 99%